Project INTERACT An Interagency Linkage System between Education and Rehabilitation - Gutterman, June K.; Todd, Julie; Central Ohio Special Education Regional Resource Center, Columbus. Ohio Resource Center for Low Incidence and Severely Handicapped ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1981)
Project INTERACT was designed to develop a local model linkage system, an interagency effort between the Ohio Rehabilitation Services Commission (RSC) and the Ohio Department of Education (ODE), Division of Special Education (DSE) to improve the joint delivery of services to severely handicapped students. It was also intended to design and/or modify student prevocational curricula/materials to prepare the severely handicapped to function in the adult world of work. Steps followed to design/implement the referral-based local level linkage system included establishing goal statement; identifying primary agencies and their mandate, purpose, and intent; identifying objectives; selecting committee participants; holding meetings; and followup. The model linkage committee addressed interagency communication, need to identify a continuum of services, and need for model referral procedures. The system was implemented in Franklin County, Ohio, by providing a specialized inservice for staff of involved agencies. To execute the programmatic linkage between education and rehabilitation, the project developed a functionally based educational level system that included a program development and evaluation process, functionally based educational level sequence, and documentation format. (YLB)
Sponsoring Agency: Ohio State Rehabilitation Services Commission, Columbus.
Sponsoring Agency: Franklin County Board of Education, Columbus, OH.
Sponsoring Agency: Ohio State Dept. of Education, Columbus.
ERIC Note: For related documents see CE 032 717-719. Project INTERACT was funded from September 29, 1980 through September 28, 1981.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Agency Cooperation; Coordination; Education; Education Work Relationship; Educational Cooperation; Prevocational Education; Program Development; Referral; School Districts; Secondary Education; Severe Disabilities; Vocational Education; Vocational Rehabilitation; Linkage -- Project Interact; Ohio (Franklin County); Reports, Descriptive